Exploring the Intention Factors of Using Online Transportation in Jakarta with Multiple Regression - Eko Retno Indriyarti; Sri Wijihastuti (Journal of Business & Applied Management, 2021)
There is still a gap in explaining the factors that influence the desire to use online transportation, especially for users from generation X and generation Y who use measurement variables of service quality, satisfaction, and government policies to be the background for this research. In addition, lifestyles surrounded by trends and popularity, for example in big cities, also shape buying patterns, especially among younger age groups. This study aims to explain and analyze the factors that influence the desire to use online transportation for users who come from generations X and Y in Jakarta. This quantitative research uses multiple regression models with Statistical Package for Social Science (SPSS) analysis tools 25. By using surveys and questionnaires compiled on a Likert scale of 1-5 on 180 respondents, this study explains that the quality of services provided by transportation service providers online influences the desire of generation X and Y in Jakarta to use online transportation. Furthermore, the results of this study explain that the overall satisfaction felt by users from generations X and Y in Jakarta has no effect on the desire to use online transportation itself. Third, the results of this study explain that government policy has no effect on the desire to use online transportation from generations X and Y in Jakarta. Simultaneously this study explains the results where the quality of services provided by online transportation service providers, perceived overall satisfaction, and government policies regarding online transportation influence the desire of generation X and Y in Jakarta to use online transportation. Dynamic competition also provides input on other variables that need to be used for previous research, such as the form of marketing strategies undertaken or the communication skills of driver partners as part of the company's human resources.